2016
DOI: 10.1242/bio.020362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxic drugs Herceptin and doxorubicin inhibit cardiac microvascular endothelial cell barrier formation resulting in increased drug permeability

Abstract: Cardiotoxicity induced by anti-cancer therapeutics is a severe, and potentially fatal, adverse reaction of the heart in response to certain drugs. Current in vitro approaches to assess cardiotoxicity have focused on analysing cardiomyocytes. More recently it has become apparent that non-cardiomyocyte cells of the heart can potentially contribute to cardiotoxicity. Herceptin and doxorubicin are known to induce cardiotoxicity in the clinic. The effect of these drugs on the endothelial tight junction barrier was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
1
46
1
Order By: Relevance
“…As a series of critical pathophysiological events of cardiovascular complications, endothelial dysfunction may cause hemorrhage, infarction, atherosclerosis, restenosis (Soultati et al, 2012;Wojcik et al, 2015). Studies have shown that Dox could downregulate CX40 (Idris-Khodja et al, 2013), MnSOD expression and activity (Koka et al, 2010;Santos-Alves et al, 2019), regulate Bcl-2/Bax ratio (Durrant et al, 2015;You et al, 2019), promote the shift from topoisomerase II a to II b (Deng et al, 2014;Damiani et al, 2018), disturb microRNA, DNA methylation or protein acetylation (Nordgren et al, 2017;Ferreira et al, 2017), affect PARP-2/SIRT (Szántó et al, 2011), VEGF pathway (Chiusa et al, 2012), and interfere with tight junction formation between cardiac microvascular endothelial cells leading to increased permeability (Wilkinson et al, 2016). In the study, we proved in vivo that, after injected Dox with the classical protocol, the mice showed the LDH and CK activities in serum increased significantly (Figures 2A, B), the inflammatory changes were observed by histopathology ( Figure 2C), which was noticeable as brown TUNEL-positive cells in microscopy ( Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…As a series of critical pathophysiological events of cardiovascular complications, endothelial dysfunction may cause hemorrhage, infarction, atherosclerosis, restenosis (Soultati et al, 2012;Wojcik et al, 2015). Studies have shown that Dox could downregulate CX40 (Idris-Khodja et al, 2013), MnSOD expression and activity (Koka et al, 2010;Santos-Alves et al, 2019), regulate Bcl-2/Bax ratio (Durrant et al, 2015;You et al, 2019), promote the shift from topoisomerase II a to II b (Deng et al, 2014;Damiani et al, 2018), disturb microRNA, DNA methylation or protein acetylation (Nordgren et al, 2017;Ferreira et al, 2017), affect PARP-2/SIRT (Szántó et al, 2011), VEGF pathway (Chiusa et al, 2012), and interfere with tight junction formation between cardiac microvascular endothelial cells leading to increased permeability (Wilkinson et al, 2016). In the study, we proved in vivo that, after injected Dox with the classical protocol, the mice showed the LDH and CK activities in serum increased significantly (Figures 2A, B), the inflammatory changes were observed by histopathology ( Figure 2C), which was noticeable as brown TUNEL-positive cells in microscopy ( Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…DOX has vascular toxicity and causes vessel impairment. 32,33 Nearly one half (approximately 41% for SCID and approximately 47% for BALB/c) of the GFP(+) Muse cells that integrated into the glomeruli expressed endothelial marker CD31(+). Turnover and replacement of endothelial cells are major mechanisms that underlie maintenance of the vascular integrity within the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an appealing concept of cardiac microvascular injury as a potential primary event that contributes to DOX-induced cardiotoxicity has recently emerged. DOX can affect the function of cardiac endothelial cell barrier by affecting the formation of tight junctions thus determining an increased vascular permeability [ 76 ].…”
Section: Vascular Cellsmentioning
confidence: 99%